FROM LANGUAGE PROFICIENCY TO LEARNER WELL-BEING: A SYSTEMATIC LITERATURE REVIEW OF WELL-BEING-ORIENTED ENGLISH LANGUAGE TEACHING - Fitri Yuliana; Faizatul Hayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student well-being in English Language Teaching (ELT) is a crucial aspect for students, as their success is measured not only by linguistic proficiency but also by their emotional state. However, studies systematically mapping the development of well-being in ELT remain limited. This study aims to identify research trends, key themes, and research gaps and future directions regarding well-being in ELT. It employs a Systematic Literature Review (SLR) methodology following PRISMA guidelines. Data were obtained from the Scopus database through a process of identification, screening, eligibility, and inclusion. Out of 1,451 initial articles identified, 17 met the inclusion criteria and were analyzed using thematic analysis. The results indicate a significant increase in publications concerning well-being in ELT since 2020. The analysis identified four key research themes: psychological factors supporting well-being; the roles of teachers and the learning environment; the relationship between well-being and language learning outcomes; and well-being as an approach within ELT theory and practice. Furthermore, existing research is predominantly characterized by specific national contexts, quantitative approaches, and a view of well-being as an outcome. These findings underscore the importance of integrating well-being into English Language Teaching